2008
DOI: 10.1111/j.1365-2648.2007.04560.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an insomnia intervention on fatigue, mood and quality of life in breast cancer survivors

Abstract: Title. Efficacy of an insomnia intervention on fatigue, mood and quality of life in breast cancer survivors Aim. This paper is a report of a study to describe the efficacy of cognitive behavioural therapy for insomnia on fatigue, mood and quality of life in breast cancer survivors. Background. Women who receive primary treatment for breast cancer often complain of insomnia. Rarely evaluated in insomnia intervention studies is the effect of cognitive behavioural treatment on the psychosocial outcomes of fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
140
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(155 citation statements)
references
References 50 publications
5
140
0
10
Order By: Relevance
“…On the other hand, problems in performing usual activities were only significantly reported among the younger women. Previous studies on the rehabilitation of breast cancer patients reported significant improvements in overall QoL after cognitive behavioral therapy (CBT) intervention against anxiety and depression (Dirksen and Epstein 2008;Savard et al 2005) as well as by pain management.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, problems in performing usual activities were only significantly reported among the younger women. Previous studies on the rehabilitation of breast cancer patients reported significant improvements in overall QoL after cognitive behavioral therapy (CBT) intervention against anxiety and depression (Dirksen and Epstein 2008;Savard et al 2005) as well as by pain management.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep hygiene recommendations include caffeine and exercise avoidance near bedtime, comfortable sleep surroundings (dark, cool, peaceful, and relaxing), and soothing activities at bedtime (reading, tranquil music). Several studies have demonstrated the benefit of behavioral therapies for sleep improvement and fatigue in long-term cancer survivors [31][32][33] . In addition, behavioral therapies may often be combined with complimentary therapies to address sleep issues.…”
Section: Sleep Therapymentioning
confidence: 99%
“…Often, depressed patients subjectively interpret their symptoms as a sign of tiredness and try to ameliorate them by seeking additional rest and sleep. However, inactivity in most cases negatively impacts mood, and some evidence exists suggesting that on the contrary behavioural activation and chronically restricting bed times might improve mood and depressive symptoms [6,7] .…”
mentioning
confidence: 99%